Hierarchy of ideals in market interactions: An application to the labor market - Aurélie Charles (Levy Economics Institute of Bard College, 2013)
This paper argues that a hierarchy of ideals exists in market interactions that sets the benchmark on the norm of fairness associated with these interactions, thus affecting pricing decisions associated with market exchange. As norms emerge, an ideal determines the criteria of optimal behavior and serves as a basis for market exchange. Norms homogenize the diversity of commodities in market interactions according to a hierarchy of norms and values. The paper then goes on to illustrate how this hierarchy of ideals works in the labor market, leading to inequality of access to jobs and wages between groups of individuals. Groups socially perceived to be diverging from the context-dependent dominant ideal are likely to suffer most in market interactions.
Keywords: B00; D1; E31; J31; J71; P00; 330; Market Exchange; Norms; Optimality; Labour Market